Little man - The Beads; PonyCanyon Entertainment (Malaysia). (Kuala Lumpur : PonyCanyon Entertainment, 1996)
Contains four pop rock tracks.
CD 1 : Little Man (album version) / (4:55) -- Sacrifice (out take) / (3:30) -- Special Day (alternate version) / (3:32) -- Little Man (acoustic version) / (4:32).
Koleksi Khas Wiramanja.
Jit Woei (lead vocals, guitars), David (guitars, backing vocals), Jacque (bass guitar).
Title from disc label.